Matti Kurikka – a prophet in his own country and abroad - Heimo, Anne; Pollari, Mikko; Rajavuori, Anna; Salmi-Niklander, Kirsti; Seppälä, Mikko-Olavi; Suodenjoki, Sami (Siirtolaisuusinstituutti, 2016)
Matti Kurikka (1863-1915) is a multi-dimensional and controversial character in Finnish history. He was a playwright, a journalist, a socialist, a Utopian and a Theosophist, as well as a speaker for free love and women’s rights. Those involved in the research project Fragmented visions. Performance, authority and interaction in early 20th-century Finnish oral-literary traditions (funded by the Academy of Finland 2014-2017, www.fragvis.net) singled out Matti Kurikka because his life concretizes both ideological tensions and performative practices in late-19th and early-20th-century Finland. Members of the project team presented their research at the FinnForum XI conference in Turku, focusing on the ethnic and transnational aspects of Matti Kurikka’s career. Mikko-Olavi Seppälä concentrated on Matti Kurikka as a playwright; Sami Suodenjoki charted his political shipwreck in 1899; Anne Heimo described his time in Queensland; Mikko Pollari covered his unsuccessful return to Finland in 1905–1909 and his multi-phased transnational career; Anna Rajavuori discussed “kurikkalaisuus” as a label for dubious policies and ideals in the Finnish labor movement; and Kirsti Salmi-Niklander focused on Kurikka’s last years and how he is remembered in the US.